The National Pact project predicting the security of Anatolia from a Turkish perspective and the intensifying Turkish-British rivalry in Northern Iraq (1920-1926) - Ada, Turhan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
The National Pact Project, which was approved by the Turkish parliament and became official on 28 January 1920, was approved by the Ottoman Assembly. It envisaged the security of the Turkish presence in the region, which considered Anatolia as the axis, and was based on the thesis that this security started in Northern Iraq and Northern Syria. There was a Turkish-British rivalry with the central theme of oil in Northern Iraq. Ultimately, the winner was England, which had military and political power. According to the Turkish side, the separatist movements that emerged in the last period after the Cold War and concentrated in the south of Turkey, especially in Northern Iraq, revealed the realistic aspect of the National Pact project, which was developed against possible security gaps. However, Turkey has never put the project into practice, and limited operations in areas close to the borderlines have been sufficient.
Keywords: England; Iraq; National Pact; Turkish foreign policy; Turkish national struggle; Area Studies